SPREADING OF CALF NEOASCAROSIS ON FARMS OF SUMY REGION - Nagorna, L. V.; Risovaniy, V. I. (Scientific Progress & Innovations, 2019)
Nematodoses are unresolved problem on cattle farms. Nematodoses have become widespread in various states and climatic zones. Neoascaris infestation is a serious problem for cattle young. Parasitizing neoasca-rises causes digestive disorders, the appearance of bronchopneumonia of parasitic etiology. Animals lag behind in growth and development, and die at high infestation intensity. The purpose of our work was to in-vestigate the spreading of calf neoascarosis on small farms of Sumy region. To achieve this goal, it was nec-essary to solve the following tasks: to carry out a laboratory study of feces, analyze the impact of anthropo-genic factors, technological schemes of animal growing, sanitary and hygienic conditions on the farms as to neoascarosis spreading. The work was performed on the basis of the laboratory of the Department of epizo-otology and parasitology of Sumy National Agrarian University, as well as on farms of Sumy region. The study was conducted on different age groups of young animals, in particular, 1–3 months, 4–5 months and 6–12 months. For coproovoscopy, a standardized flotation method by Kotelnikov and Khrenov with ammo-nium nitrate solution was used. According to the results of the researches, the spreading of calf neoascarosis on the farms of Sumy region was established. The average prevalence on the surveyed farms made 61 %. Of the 112 studied animals of different age categories, 69 were found to be infected with Neoascaris vitulorum. The maximum disease manifestation in young animals was observed in the spring-autumn period. It has been found that in case of calf neoascarosis, the prevalence indices have decreased with age. Calves 1-3 months of age were infected by calf Neoascaris vitulorum most of all (prevalence made 84.8 %). In the group of calves aged 4–5 months, the prevalence was lower and made 62.9 %. The lowest prevalence (25.8 %) was diagnosed in the calf group aged 6−12 months.